The Spawning of Koi (Cyprinus carpio) using Semi-Artificial Method: The Observation of Fecundity, Fertilization Rate and Hatching Rate - Akbar Maulana Al Ishaqi; Putri Desi Wulan Sari (JURNAL PERIKANAN DAN KELAUTAN, 2019)
Semi-artificial spawning is spawning which is done by providing hormonal stimulation to the boordstock, but the process of ovulation occurs naturally. This study aims to determine the fecundity, Fertilization Rate (FR), and Hatching Rate (HR) in koi fish spawned by the semi-artificial spawning method. Spawning was done by injecting ovaprim dose 0.5 ml / kg broodstock weight. Spawning was done three times for the three type of Koi broodstock. Spawning I for the broodstock of Platinum (1.2 kg), spawning II for the broodstock of Shiro (2.4 kg), and spawning III for the broodstock of Sanke (2.2 kg). Fecundity obtained from spawning I to III were 100.000, 250.000 and 300.000, respectively. The fertilization Rate (FR) obtained from spawning I to III were 78%, 83%, and 71%, respectively. Hatching Rate (HR) obtained from spawning I to III were 42%, 67%, and 61%, respectively